Daily Living Performance in Schizophrenic Patients in Correlation with Positive and Negative Symptoms - Nurul Amelia Rahayu Putri; Tuti Kurnianingsih; Santi Andayani (Althea Medical Journal, 2020)
Background: Schizophrenia is a global mental health problem. Patients experience problems in their daily-living performance. Positive and negative symptoms have been part of characteristics of schizophrenia that are absent in normal individuals, which include a distinctive fundamental distortion of thoughts and perception (positive symptoms) and loss of normal function and behavior (negative symptoms). This study aimed to explore the correlation between positive and negative symptoms and daily-living performance in schizophrenia. Methods: A correlative analytical study with a cross-sectional approach was conducted using secondary data from the Outpatient Clinic of the Mental Hospital of West Java Province. Data on socio-demographic characteristics were collected and positive and negative symptoms as assessed by Positive and Negative Syndrome Scale or Subscales (PANSS) were correlated with the activities of daily living (ADLs) and instrumental activities of daily living (IADLs), which were further analyzed by Spearman’s correlation test.Results: In total, 31 male schizophrenic patients aged between 24-45 years old. There was no significant correlation between ADLs dependency levels and both positive and negative symptoms. However, there was a significant correlation between IADLs function and positive symptoms and not with negative symptoms.Conclusions: Even though no correlation was identified between ADLs dependency levels with positive and negative symptoms, the ADLs and IADLs assessments should be considered as important tools for schizophrenic patients for rehabilitation to improve daily-living functioning.